Microsatellite instability in early sporadic breast cancer. - Shaw, J. A. (Nature Publishing Group, 1996)
We have studied the incidence of microsatellite instability at three trinucleotide repeats and seven dinucleotide repeats from five chromosomal regions, in a group of 30 mammographically detected 'early' invasive breast cancers and correlated its occurrence with clinicopathological parameters. The myotonic dystrophy (DM-1) trinucleotide repeat was analysed in 48 additional cases. In 4 out of 78 (5%) paired tumour-normal DNA samples we found evidence of somatic microsatellite instability at DM-1: a novel allele of a different size was seen in the tumour DNA which was not present in the normal DNA sample. All four tumours that showed evidence of instability were from the core group of 30 cases (13%) and were well or moderately differentiated, oestrogen receptor-positive, infiltrating ductal carcinomas. Two of these tumours were unstable at nine of ten loci studied, both trinucleotide and dinucleotide repeats. DNA prepared from different normal tissues showed no evidence of instability, for all four instability cases. These data indicate that microsatellite instability is specific to the tumour DNA and is an early event in the genesis of some sporadic breast cancers. IMAGES: